Dmitri the astronaut - Agee, Jon (HarperCollins, 1998)
Astronaut Dmitri returns home after two-and-a-half years on the moon to find that people have forgotten all about him, but his lunar pal Lulu, who has stowed away in Dmitri's bag of rocks, jogs everyone's memory.